2011
DOI: 10.1111/j.1365-2230.2011.04091.x
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of meeting nutritional requirements in children and adults with epidermolysis bullosa: proceedings of a multidisciplinary team study day

Abstract: Summary This is a report of a study day held in London on 3 March 2010 to discuss measures with which to meet the nutritional requirements of patients with epidermolysis bullosa (EB). Members of national and international multidisciplinary teams (MDTs) caring for patients with EB attended this event. The study day focused on four challenging aspects of management intimately associated with nutritional status in EB, necessitating close cooperation between MDT members: iron‐deficiency anaemia, gastrostomy placem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 5 publications
1
41
0
3
Order By: Relevance
“…Our study findings are consistent with several published smaller reviews and case-series, which all indicate anemia is prevalent in EB patients Fridge and Vichinsky, 1998, Hubbard et al, 2011, Kuo et al, 2006, Van den Akker et al, 2009. 54% of JEB-GS patients in a small longitudinal retrospective study ( n = 22) performed in Netherlands were reported to have anemia as one complication, without going into details as to severity [20].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study findings are consistent with several published smaller reviews and case-series, which all indicate anemia is prevalent in EB patients Fridge and Vichinsky, 1998, Hubbard et al, 2011, Kuo et al, 2006, Van den Akker et al, 2009. 54% of JEB-GS patients in a small longitudinal retrospective study ( n = 22) performed in Netherlands were reported to have anemia as one complication, without going into details as to severity [20].…”
Section: Discussionsupporting
confidence: 92%
“…Hubbard et al (Hubbard et al, 2011) found that 96% ( n = 52/54) of pediatric RDEB patients were anemic in a cross-sectional study conducted in a multidisciplinary team study day in London. This study was limited to more severe patients already seeing a dietician and multidisciplinary team.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Malnutrition leads to failure to thrive, delayed puberty, and anemia, a cascade of clinical and biological events, further affecting wound healing and increasing skin breakdown. 15-17 Low protein intake or relative deficiency can prevent the production of granulation tissue contributing to “stalled” healing. 18 Albumin levels, a gross indicator of long-term nutritional deficit, less than 2.0 to 3.0 g/dL (normal: 3.0-5.4 g/dL) 19 are associated with impaired healing.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, an insufficient fluid and fibre intake frequently causes constipation, which can induce painful defecation (anal fissures). Overall, nutritional compromise is more important in generalized forms of RDEB and JEB [80-82]. …”
Section: Care Of the Eb Newborn And Infantmentioning
confidence: 99%